Forensic psychology the basics - Taylor, Sandra (The basics, 2015)
This text provides an engaging overview to the core topics within Forensic Psychology, guiding the reader through this exciting and popular discipline. Combining a discussion of theory with information about the role of a professional forensic psychologist